Specific physical development of midfielders in comparative football from youth to senior level: insight from objective parameters measured with advanced wearable technology - Izzo, R.; Catani, A.; Cejudo, A.; Cruciani, A.; Giovannelli, M.; Hosseini, C.; Crudelini, E. (Journal of Physical Education and Sport, 2025)
Although relatively unederrpresented in scientific literature, this study aims to establish foundational insights into the developmental trajectory of midfield football players as they transition from youth to senior levels. The research primarily examines physical and athletic attributes while also considering their interaction with specific technical and tactical aspect. The study focuses on players aged 14-23 years.The limited existing research on this topic has, hindered comparative analysis but also created an opportunity to explore an underexamined area. This investigation uses wearable scientific instrumentation (K-AI, K-Sport Ita) to provide new insights into player development.The param under scrutiny encompass a spectrum of physical attributes, including distance covered, speed dynamics, acceleration, and deceleration patterns. Of particular interest is the evaluation of High Peak Speed (HPS), denoting the pinnacle of instantaneous velocity within defined temporal intervals. Furthermore, the discerning factor in an athlete's developmental journey lies not solely in their maximal speed potential, but rather in their capacity to sustain high-intensity sprints and consistently surpass the HPS threshold during match scenarios (Izzo et al., 2018). This nuanced perspective emerges as a pivotal and discerning criterion for assessing the prowess of football athletes.